Residential Exposure to Traffic-Related Air Pollution and Survival after Heart Failure - Medina-Ramón, Mercedes; Goldberg, Robert; Melly, Steven; Mittleman, Murray A.; Schwartz, Joel (Environmental health perspectives, 2008)
Background: Although patients with heart failure (HF) have been identified as particularly susceptible to the acute effects of air pollution, the effects of long-term exposure to air pollution on patients with this increasingly prevalent disease are largely unknown. Objective: This study was designed to examine the mortality risk associated with residential exposure to traffic-related air pollution among HF patients. Methods: A total of 1,389 patients hospitalized with acute HF in greater Worcester, Massachusetts, during 2000 were followed for survival through December 2005. We used daily traffic within 100 and 300 m of residence as well as the distance from residence to major roadways and to bus routes as proxies for residential exposure to traffic-related air pollution. We assessed mortality risks for each exposure variable using Cox proportional hazards models adjusted for prognostic factors. Results: After the 5-year follow-up, only 334 (24%) subjects were still alive. An interquartile range increase in daily traffic within 100 m of home was associated with a mortality hazard ratio (HR) of 1.15 [95% confidence interval (CI), 1.05-1.25], whereas for traffic within 300 m this association was 1.09 (95% CI, 1.01-1.19). The mortality risk decreased with increasing distance to bus routes (HR = 0.88; 95% CI, 0.81-0.96) and was larger for those living within 100 m of a major roadway or 50 m of a bus route (HR = 1.30; 95% CI, 1.13-1.49). Adjustment for area-based income and educational level slightly attenuated these associations. Conclusions: Residential exposure to traffic-related air pollution increases the mortality risk after hospitalization with acute HF. Reducing exposure to traffic-related emissions may improve the long-term prognosis of HF patients.